Interventions to support the psychological empowerment of nurses: a scoping review - Huang, Liebin; Liu, Ming; Wang, Xin; Hsu, Meihua (Frontiers in Public Health, 2024)
BackgroundEstablishing an empowering work environment is significantly contributing to nurse’s job satisfaction, performance, retention, and organizational success. This study aimed to conduct a scoping review to chart and synthesize current research on interventions to support nurses’ psychological empowerment.MethodsTen databases were searched, including PubMed/Medline, Web of Science, Scopus, Embase, EBSCOhost, Cochrane Library, CNKI, Wanfang, VIP, and OpenGrey, following the Joanna Briggs Institute’s methodology for scoping reviews. The search encompassed literature from its inception to 5 September 2024. The selection of studies followed predetermined inclusion and exclusion criteria. A manualized systematic quality assessment method was applied to the included studies, and the extracted data were charted using a series of tables.ResultsEleven studies were included. Seven studies reported the theoretical framework used. The interventions are all educational and are divided into two main sections: theoretical learning and applied practice. The duration of the interventions spanned a wide range of hours. The intervention format was based on offline training. The participants included both nurse managers and nurses. The evaluation measures were mostly multiple time points using the Spreitzer Psychological Empowerment Instrument. The interventions were generally effective, although some studies reported different results.ConclusionResearch on psychological empowerment interventions for nurses is still in the developmental phase, with preliminary evidence validating their positive effects. Future research should focus on conducting randomized controlled studies with larger sample sizes, selecting appropriate theoretical frameworks to design interventions, enriching the content and form of interventions, and strengthening evaluation measures to improve the quality of psychological empowerment interventions for nurses.Systematic review registrationOSF, https://doi.org/10.17605/OSF.IO/W7ZG6.